Unique dynamic profiles of social attention in autistic females. (30th May 2022) - Del Bianco, Teresa; Mason, Luke; Lai, Meng‐Chuan; Loth, Eva; Tillmann, Julian; Charman, Tony; Hayward, Hannah; Gleissl, Teresa; Buitelaar, Jan K.; Murphy, Declan G.M.; Baron‐Cohen, Simon; Bölte, Sven; et al.
Abstract : Background: Social attention affords learning opportunities across development and may contribute to individual differences in developmental trajectories, such as between male and female individuals, and in neurodevelopmental conditions, such as autism. Methods: Using eye‐tracking, we measured social attention in a large cohort of autistic ( n = 123) and nonautistic females ( n = 107), and autistic ( n = 330) and nonautistic males ( n = 204), aged 6–30 years. Using mixed Growth Curve Analysis, we modelled sex and diagnostic effects on the temporal dynamics of proportional looking time to three types of social stimuli (lean‐static, naturalistic‐static, and naturalistic‐dynamic) and examined the link between individual differences and dimensional social and nonsocial autistic traits in autistic females and males. Results: In the lean‐static stimulus, average face‐looking was higher in females than in males of both autistic and nonautistic groups. Differences in the dynamic pattern of face‐looking were seen in autistic vs. nonautistic females, but not males, with face‐looking peaking later in the trial in autistic females. In the naturalistic‐dynamic stimulus, average face‐looking was higher in females than in males of both groups; changes in the dynamic pattern of face looking were seen in autistic vs. nonautistic males, but not in females, with a steeper peak in nonautistic males. Lower average face‐looking was associated with higher observer‐measured autistic characteristics in autistic females, but not in males. Conclusions: Overall, we found stronger social attention in females to a similar degree in both autistic and nonautistic groups. Nonetheless, the dynamic profiles of social attention differed in different ways in autistic females and males compared to their nonautistic peers, and autistic traits predicted trends of average face‐looking in autistic females. These findings support the role of social attention in the emergence of sex‐related differences in autistic characteristics, suggesting an avenue to phenotypic stratification.